How green is manufacturing? Status and prospects of national green industrialisation. The case of Morocco. (2018) - Alba, Jaime Moll De; Todorov, Valentin
This paper reviews the concept of green industry. Our study introduces an innovative methodology to analyse green industrial development at country level by constructing an original database and looking at both green industrial production and employment data derived from UNIDO's industrial statistics database (INDSTAT). We use our methodological approach to review the status and analyse the prospects of green industrialisation in a selected set of countries. We conclude that countries have not seized yet the opportunities offered by green industry. We undertake a closer analysis of the green performance of Morocco, a country that has failed in the past to boost industrial development despite having put in place an ambitious green industrial policy. Our analysis suggests that green industrialisation offers an untapped potential that developing countries might use in the future as an alternative path to operate their structural transformation within the framework of the existing international industrial development setting.